Coffee and tea consumption and the risk of ovarian cancer: a prospective cohort study and updated meta-analysis. - Braem, MG; Onland-Moret, N; Schouten, L; Tjønneland, A; Hansen, L; Dahm, C; Overvad, K; Lukanova, A; Dossus, L; Floegel, A; Boeing, H; Clavel-Chapelon, F; et al. (2012)
BACKGROUND: In 2007 the World Cancer Research Fund Report concluded that there was limited and inconsistent evidence for an effect of coffee and tea consumption on the risk of epithelial ovarian cancer (EOC). OBJECTIVE: In the European Prospective Investigation into Cancer and Nutrition (EPIC), we aimed to investigate whether coffee intakes, tea intakes, or both are associated with the risk of EOC. DESIGN: All women participating in the EPIC (n = 330,849) were included in this study. Data on coffee and tea consumption were collected through validated food-frequency questionnaires at baseline. HRs and 95% CIs were estimated by using Cox proportional hazards models. Furthermore, we performed an updated meta-analysis of all previous prospective studies until April 2011 by comparing the highest and lowest coffee- and tea-consumption categories as well as by using dose-response random-effects meta-regression analyses. RESULTS: During a median follow-up of 11.7 y, 1244 women developed EOC. No association was observed between the risk of EOC and coffee consumption [HR: 1.05 (95% CI: 0.75, 1.46) for the top quintile compared with no intake] or tea consumption [HR: 1.07 (95% CI: 0.78, 1.45) for the top quintile compared with no intake]. This lack of association between coffee and tea intake and EOC risk was confirmed by the results of our meta-analysis. CONCLUSION: Epidemiologic studies do not provide sufficient evidence to support an association between coffee and tea consumption and risk of ovarian cancer.